Retinal gap junctions are involved in rhythmogenesis of neuronal activity at remote locations – Study on infra-slow oscillations in the rat olivary pretectal nucleus - Orlowska-Feuer, Patrycja; Jeczmien-Lazur, Jagoda S.; Szkudlarek, Hanna J.; Lewandowski, Marian H. (Neuroscience, 2016)
•Pharmacological blockade of retinal gap junctions with CBX or MFA leads to abolition of infra-slow oscillations in the OPN.•The effect of CBX on light-induced responses of the OPN oscillatory cells is GJs independent.•Retinal synchrony might be crucial for the expression of the infra-slow rhythm at remote locations. A subpopulation of olivary pretectal nucleus (OPN) neurons fire action potentials in a rhythmic manner with an eruption of activity occurring approximately every two minutes. These infra-slow oscillations depend critically on functional retinal input and are subject to modulation by light. Interestingly, the activity of photoreceptors is necessary for the emergence of the rhythm and while classic photoreceptors (rods and cones) are necessary in darkness and dim light, melanopsin photoreceptors are indispensable in bright light. Using pharmacological and electrophysiological approaches in vivo, we show that also blocking retinal gap junctions (GJs), which are expressed by multitude of retinal cells, leads to the disruption of oscillatory activity in the rat OPN. Intravitreal injection of carbenoxolone (CBX) quenched oscillations in a concentration-dependent manner with 1mM being ineffective, 5mM showing partial and 20mM showing complete effectiveness in disrupting oscillations. Moreover, the most effective CBX concentration depressed cone-mediated light-induced responses of oscillatory neurons suggesting that CBX is also acting on targets other than GJs. In contrast, intravitreal injection of meclofenamic acid (MFA, 20mM) led to disruption of the rhythm but did not interfere with cone-mediated light-induced responses of oscillatory neurons, implying that MFA is more specific toward GJs than CBX, as suggested before. We conclude that electrical coupling between various types of retinal cells and resultant synchronous firing of retinal ganglion cells is necessary for the generation of infra-slow oscillations in the rat OPN.